Sustainable Management and Development of Religious Tourism in Ramayana Circuit of Uttar Pradesh (Journal of Informatics Education and Research, 2026)
Over the last decade, India has witnessed substantial growth in religious tourism, largely propelled by state-sponsored initiatives, including the creation of thematic tourism circuits. Among these, the Ramayana Circuit, developed under the Swadesh Darshan Scheme, holds a distinctive position because of its profound civilizational, spiritual, and cultural importance within Hindu belief systems. Despite rising tourist arrivals, the circuit's long-term sustainability is constrained by fragmented governance, inadequate accommodation, and erosion of authentic spiritual ambiance. Drawing on servicecape theory, destination governance literature, and sustainability discourse, this study proposes and empirically validates an integrated framework, FITSL-Gov (Familiarity, Interaction and Ambience, Tourism Infrastructure, Service and Sustainability, Loyalty, and Governance). Using a mixed-methods design, quantitative data were collected from 600 pilgrims across five key nodes of the Ramayana Circuit (Ayodhya, Nandigram, Shringverpur, Prayagraj, and Chitrakoot, complemented by qualitative insights from 42 stakeholder interviews. The structural equation modeling results indicate that spiritual ambiance is the strongest mediator between accommodation quality, governance effectiveness, and tourist satisfaction and loyalty, which is consistent with previous pilgrimage studies. The findings further reveal a governance paradox, in which individual initiatives receive high ratings but fail to convert into holistic destination satisfaction due to coordination gaps. This study contributes to the literature by encompassing the servicecape and destination loyalty models in religious tourism contexts and offering actionable policy recommendations for ambiance-centric planning, tiered accommodation development, and cohesive governance reforms. This study provides a data-driven roadmap for positioning the Ramayana Circuit as a globally competitive, spiritually authentic, and sustainably managed religious tourism destination.